Makna Sufistik Tanda-Tanda Kata Isim (Nomina) Pada Ilmu Nahwu Dalam Kitab Alfiyah Ibnu Malik (Analisis Semiotika Roland Barthes) - Zarkasyi, Muhamad Qustulani (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2023)
This paper discusses (1) Roland Barthes' semiotic theory; and (2) its application in finding the Sufistic meaning of the signs of the word ism (noun) in nahwu science in the Alfiyah book by Ibn Malik. This research is a qualitative descriptive literature (library) with Roland Barthes's semiotic approach, in which the text is considered autonomous from its author (the dead of author), and the meaning is divided into how many levels. Therefore, this study concludes that (1) Roland Barthes' semiotic theory opens opportunities for multilevel meanings, where the first level is called denotation, and the second level is called connotation. The meaning of each is influenced by the imagination and feelings as well as socio-historical and mythological readers; and (2) the autonomization of the text makes the meaning which originally meant